ANALISIS DAYA TAMPUNG DAN DAYA SERAP TENAGA KERJA PADA SEKTOR EKONOMI DI INDONESIA - Mauliani, Ba’dillatifa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Population growth continues to rise in Indonesia of course coupled with the growth in the total labor force which is a problem in the face in Indonesia. So the availability of jobs is not balanced with the rate of population growth each year has increased rapidly and dynamically. The capacity and absorption in the economic sector is a focus on accommodating capacity of each economic sector in accommodating the workforce. Absorption of labor and see the value of elasticity in every sector of the economy to be able to determine which sector has the potential to absorb a lot of labor and is able to expand employment. In Indonesia, the sector that has the capacity to accommodate the workforce in large numbers, namely the tertiary sector amounted to 44.18%. Meanwhile, according to the capacity of the labor islands pretty much in the primary sector, such as Sumatra island, Borneo island, Sulawesi island, Bali and Nusa Tenggara island, Makulu Island and papua island. Furthermore, the amount of absorption of labor the highest elasticity value of 0.94 the primary sector. For each island of the value of the highest elasticity are in the primary sector,such as Java, Bali and Nusa Tenggara and Papua. The next highest elasticity values that are in the secondary sector,such as Sumatra island, Sulawesi island and Kalimantan island. For the highest elasticity values that are in the tertiary sector is Maluku island.Keywords: Economy Sector, Unemployment, Elasticity Of Employment Opportunities.